SNP Loci and Favorable Haplotype Mining for Alkalinity Tolerance in the Rice Bud Stage - Zhenzhen Zhou; Mingyu Du; Zhengbo Liu; Yingping Chang; Mengyuan Xiong; Hao Sun; Xianping Cheng; Yanan Zhang; Jinghan Sun; Rui Wang; Mengyuan Zhang; Xinru Li; et al. (Agronomy, 2023)
The mining of favorable SNP loci and haplotypes is of great significance for the further cloning and molecular-assisted breeding of alkalinity-tolerance genes in rice. To improve the utilization rate of saline–alkaline lands and the yield of rice, we used the 1,322,884 SNPs obtained from the sequencing 173 of rice accessions in this study. Alkalinity-tolerance-related traits, including the germination energy (GE), germination rate (GR), seedling length (SL), root length (RL), relative alkaline damage rate (RADR) of the GERADR of the GR, RADR of the SL and RADR of the RL, were evaluated in 2019 and 2020 and revealed abundant phenotypes in the studied population. A genome-wide association analysis detected 10 quantitative trait loci (QTLs) related to alkalinity tolerance. In addition, a transcriptome sequencing analysis of the alkalinity-tolerant rice variety ‘Yuedao 9’ and the alkali-sensitive rice variety ‘Tijin’ under alkalinity stress and control conditions was performed. Three candidate genes that were predicted to be related to alkalinity tolerance in rice, namely LOC_Os06g06600, LOC_Os011g44680 and LOC_Os011g44600, were screened based on gene annotation, coding sequences and haplotype analysis. The results of this study provide important genetic information for the molecular improvement of rice.